2021
DOI: 10.1016/j.apsb.2021.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorods-mediated efficient synergistic immunotherapy for detection and inhibition of postoperative tumor recurrence

Abstract: Tumor recurrence after surgery is the main cause of treatment failure. However, the initial stage of recurrence is not easy to detect, and it is difficult to cure in the late stage. In order to improve the life quality of postoperative patients, an efficient synergistic immunotherapy was developed to achieve early diagnosis and treatment of post-surgical tumor recurrence, simultaneously. In this paper, two kinds of theranostic agents based on gold nanorods (AuNRs) platform were prepared. AuNRs and quantum dots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Nanomaterials have a large surfaceto-volume ratio and allow CTC isolation at high specificity and CTC detection at high sensitivity by adsorbing numbers of targeting ligands to bind specific molecules on cancer cells. At present, studies have reported many types of nanomaterials (Table 2) for CTC detection, including magnetic nanoparticles [213][214][215][216][217] , gold nanoparticles [218][219][220] , and quantum dots [221][222][223] . For example, studies have shown that the utilization of tannic acidfunctionalized magnetic nanoparticles 214 , CoFe2O4@Ag magnetic nanohybrids 216 , and peptide-based magnetic nanoparticle 213 , enhances the capture efficiency of CTCs in breast cancer patients.…”
Section: Recent Ctc-related Technologies: Microfluidic-based and Nano...mentioning
confidence: 99%
“…Nanomaterials have a large surfaceto-volume ratio and allow CTC isolation at high specificity and CTC detection at high sensitivity by adsorbing numbers of targeting ligands to bind specific molecules on cancer cells. At present, studies have reported many types of nanomaterials (Table 2) for CTC detection, including magnetic nanoparticles [213][214][215][216][217] , gold nanoparticles [218][219][220] , and quantum dots [221][222][223] . For example, studies have shown that the utilization of tannic acidfunctionalized magnetic nanoparticles 214 , CoFe2O4@Ag magnetic nanohybrids 216 , and peptide-based magnetic nanoparticle 213 , enhances the capture efficiency of CTCs in breast cancer patients.…”
Section: Recent Ctc-related Technologies: Microfluidic-based and Nano...mentioning
confidence: 99%
“…Moreover, cytokines loaded onto AuNPs not only avoid systemic inflammatory reactions, but their release can also be controlled. For example, Zhang et al utilised the photothermal properties of AuNPs to regulate the release of cytokine IFN-γ, resulting in approximately 59% cumulative release over 96 h. This approach significantly inhibits postoperative recurrence of lung cancer [ 228 ]. Moreover, when combined with IFN-γ, AuNPs exhibit a synergistic effect with ICIs.…”
Section: Application In Cancer Immunotherapymentioning
confidence: 99%
“…Surgery is currently the main modality to eliminate breast cancer in clinical practice, but recurrence and metastasis after surgery are still common 1 , 2 . Due to incomplete resection, residual tumors in surgical incision are tiny, scattered, and difficult to be targeted by postoperative intervention of conventional chemotherapy or radiotherapy 3 , 4 . Immunotherapy that harnesses the host's own immunity to recognize and attack the residual tumors is a promising option 5 , 6 , 7 , but still plagued with postsurgical challenges.…”
Section: Introductionmentioning
confidence: 99%